2015
DOI: 10.3906/yer-1407-12
|View full text |Cite
|
Sign up to set email alerts
|

Estimating depth to the bottom of magnetic sources at Wikki Warm Spring region, northeastern Nigeria, using fractal distribution of sources approach

Abstract: The Wikki Warm Spring (WWS) is located on the Kerri-Kerri formation of tertiary age. This forms part of the Benue Basin, which links up with the Chad Basin in the north and extends southwest to the Anambra Basin in Nigeria. The stratigraphy of the WWS region consists of alluvium, the Kerri-Kerri formation, the Gombe formation, the Pindiga formation, the Yolde formation, the Bima formation, and basement rocks as the oldest. We estimate the depth to the bottom of magnetic sources (DBMS) in the WWS region using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 69 publications
(137 reference statements)
2
28
0
Order By: Relevance
“…Critical observations from values in Table 1 show that the heat flow and geothermal gradient increase as the Curie depth decreases. This trend agrees with the results obtained by another researcher who estimated an average Curie depth in Wikki Warm Spring, located in parts of Benue basin, which links up the Chad Basin in the north to be10.72 km, with an average thermal gradient of 54.11°C/km and average heat flow values of 135.28 mWm -2 [2]. It was reported that heat flow close to 60 mWm -2 is required for considerable generation of geothermal energy, while values ranging from 80 to 100 mWm -2 and above indicate anomalous geothermal condition [22].…”
Section: Discussionsupporting
confidence: 92%
“…Critical observations from values in Table 1 show that the heat flow and geothermal gradient increase as the Curie depth decreases. This trend agrees with the results obtained by another researcher who estimated an average Curie depth in Wikki Warm Spring, located in parts of Benue basin, which links up the Chad Basin in the north to be10.72 km, with an average thermal gradient of 54.11°C/km and average heat flow values of 135.28 mWm -2 [2]. It was reported that heat flow close to 60 mWm -2 is required for considerable generation of geothermal energy, while values ranging from 80 to 100 mWm -2 and above indicate anomalous geothermal condition [22].…”
Section: Discussionsupporting
confidence: 92%
“…It has been applied in Turkey (Dolmaz et al 2005), Nigeria (Kasidi and Nur 2012), South Africa (Nyabeze and Gwavava 2016) and East and South East Asia (Tanaka et al 1999). The Fractal method has been applied in South Africa (Nyabeze and Gwavava 2018), Central India (Bansal et al 2013), Western USA (Bouligand et al 2009), Germany (Bansal et al 2011), Nigeria (Abraham et al 2015) and Mexico (Espinosa-Cardeña et al 2016).…”
Section: Spectral Statistical Methodsmentioning
confidence: 99%
“…The centroid method is based on mechanical statistical principles (Spector and Grant 1970), and on the assumption that the magnetic anomalies constitute an uncorrelated random distribution of magnetic sources (Abraham et al 2015;Bansal et al 2010Bansal et al , 2011. The power spectrum of the reduced to the pole, magnetic anomalies is defined as (Blakely 1996;Spector and Grant 1970): where h is the mean depth to the top of the magnetic source ensemble, t is the thickness of the magnetic ensemble, M is the magnetic moment, S 2 (k, a, b) is a function of the magnetic ensemble mean horizontal dimensions (a, b), k corresponds to the radial wave number in cycles/km, and Cm = 10 −7 is the proportionality constant to transform Eq.…”
Section: Centroid Methodsmentioning
confidence: 99%
See 2 more Smart Citations